THE ISSUES OF FLEXIBILITY FOR STUDENTS IN ASYNCHRONOUS LEARNING AT ENGLISH EDUCATION DEPARTMENT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Muhammad Zia ul Haq; AdhyPutra, Achmad Pangeran; Akib, Erwin (FKIP Unismuh Makassar, 2021)
The research question in this research is how effective classroom learning is using asynchronous learning with the purpose to determine the effectiveness of learning in class by observing students' ability to accept and understand a material with asynchronous method. The research method in this research uses a qualitative descriptive methodology. Descriptive qualitative research method is a non-experimental research method that is relatively easy. This research method is used to describe qualitative data obtained related to the state of the subject of a population. The participants in this study are English education students Muhammadiyah University in Makassar. Purposive sampling is use by the researcher at this time. The result of the research reveal that , it can be said that online learning is effective because of the data obtained by many existing courses. using asynchronous learning methods in learning, namely by using Google Classroom as a learning application that is often used because it has many features that greatly support the effectiveness of learning and some student opinions from interviews regarding the effectiveness of online asynchronous learning.